Quality of life tools to inform co-design in the development of assistive technologies for people with dementia and their carer - Craven, Michael P.; De Filippis, Maria Laura; Dening, Tom (Springer Verlag, 2014)
A number of tools exist to measure quality of life (QoL) for people with dementia (PwD). A selection of existing measures are summarised, obtained from an online literature survey, comprising of scales administered either by healthcare professionals with the PwD (self-report) and/or their carers (proxy report) or from observation. It is suggested that a combination of such tools with user satisfaction questionnaires may provide a way to approach the problem of evaluating Assistive Technology (AT) solutions or inform co-design of technological solutions with PwD and their carers.